Editorial - Anna Oksiutycz (Communicare)
In 2013 two University of Johannesburg professors Nina Overton-de Klerk and Sonja Verwey published an article in Communicatio “Towards an emerging paradigm of strategic communication: Core driving forces” where they argued that a shift in communication theory and practice was taking place that had a profound impact on the role of communication practitioners in business and society. The same year the University of Johannesburg introduced the first BA Strategic Communication degree in South Africa. Sadly, prof Verwey passed away in 2019. In March 2023 the Department of Strategic Communication held a memorial lecture for Prof Sonja Verwey with Prof Nina Overton-de Klerk delivering the keynote lecture, where she revisited the assumptions, theses and developments in the discipline of strategic communication during the decade since the article was published. The lead article in this issue "Reflections on the current state and future of strategic communication as paradigm and practice” is based on that lecture. In the article, Overton-de Klerk provides a review of paradigm shifts in strategic communication since 2013, considers the effect of global disruption in recent years and offers the prognosis for the future of the discipline.